Sebaceous carcinoma of eyelid treated with definitive radiotherapy with eye shield - Huang, Sheng-Yao; Chen, Yi-Wei; Liao, Yen-Hsiang; Wu, Chen-Ta; Wang, Tzu-Hwei; Hsu, Wen-Lin; Liu, Dai-Wei (Therapeutic Radiology and Oncology, 2018)
Sebaceous carcinoma is a rare malignancy, accounting for 1–5.5% of eyelid malignancy. When local excision is even not feasible, definitive radiotherapy (RT) may be considered as an alternative. An 84-year-old woman, with initial presentation of right eye pain, suffered from a papillary tumor on right upper eyelid, 3.5 cm × 0.6 cm in size. Excision biopsy revealed sebaceous carcinoma. Image studies excluded regional and distant metastasis. Definitive RT with 54 Gy, 1.8 Gy per fraction, 5 days per week, using tungsten eye shield was delivered. The radiation dose of cornea, lens and retina was compared to the dose constraint recommended by studies from Radiation Therapy Oncology Group (RTOG). We used 6 cm × 6 cm cone, with 6 MeV electron beam irradiation, water phantom and ion chamber to measure the dose. The daily dose after using eye shield was 14.4, 35.9 and 1.7 cGy to cornea, lens and retina, respectively, compared to 210.8, 231.5 and 8.03 cGy without eye shield use, respectively. Eye shield masked the radiation dose about 93.2% and 79.9% to cornea and lens, respectively. Eye shield could mask extra radiation to cornea and retina and should be used for RT of eyelid tumor.